Theory of Planned Behavior (TPB) Analysis: A Systematic Review of Key Factors of SMEs Financial Planning Behavior - Murdiono, Ahmad; Winarno, Agung; Pratikno , Heri (Journal of International Accounting, Taxation and Information Systems, 2024)
Economic challenges are closely linked to discussions about micro, small, and medium enterprises (SMEs) due to their vital role in GDP contribution and job creation. Despite this, the progress of small businesses evolving into sustainable entities has been sluggish over the last decade. Therefore, it is crucial to conduct research aimed at bolstering the capabilities of SMEs in Indonesia. This research examines the financial behavior of SMEs through a Systematic Literature Review (SLR) approach. The goal is to pinpoint the factors that affect SMEs' financial behavior and their implications for financial planning. The SLR process consists of three key stages: identification, selection, and synthesis, with this study analyzing 15 pertinent articles. The results indicate that financial behavior is shaped by various factors, such as financial literacy, financial satisfaction, financial socialization, and mental accounting. This research serves as a resource for stakeholders in the SME sector, including researchers, practitioners, and policymakers, to enhance the capabilities of SMEs in Indonesia. Additionally, the findings aim to contribute to the global financial literature by offering a more organized behavioral finance model.